A membership pricing policy to facilitate service scale-expansion. Issue 3 (12th March 2017) - Hung, Hui-Chih; Chung, Chung-Yu; Wu, Muh-Cherng; Shen, Wan-Ling
ABSTRACT: This paper proposes a multi-year membership pricing policy for a service business like a gym chain. In the pricing policy, the equivalent membership price per year is relatively low to attract customers, and the multi-year membership fees must be prepaid in full. The prepaid cash provides resources for scale-expansion by opening new stores. We develop a nonlinear mixed integer programming model to formulate the pricing decisions. Numerical experiments reveal that the multi-year membership pricing policy, from a long-term perspective, is substantially better than the business-as-usual pricing policy (1-year membership) in cash balance, profit, and market share. Yet, the performances of the two pricing policies do not differ much from a short-term perspective. These findings indicate that the multi-year pricing policy may be a good strategy, because it initially attracts less attention of competitors; suddenly it emerges and substantially outperforms its competitors in cash balance, profit, and market share.